CURRENT CHALLENGES AND PROSPECTS OF UNIVERSITY HISTORY EDUCATION IN THE REPUBLIC OF BELARUS (EDUCATION IN THE 21ST CENTURY, 2025)
The article is devoted to the study of current trends, challenges and opportunities facing the system of higher historical education in the Republic of Belarus. The potential of university historical education for improving the quality of training specialists-historians under modern educational and social changes is substantiated.The purpose of the article is to analyze current challenges and identify promising directions for the development of university historical education in the Republic of Belarus.Relevance of the research. Studying the current challenges and prospects of university historical education in the Republic of Belarus is extremely important amidst contemporary social, political, and economic transformations. Historical education plays a key role in shaping civic identity, patriotism, and cultural awareness among young people. However, in recent years, the system of university historical education has faced numerous challenges related to changes in the perception of history, the influence of information technologies, as well as the need to meet international standards of education quality. All these factors require deep analysis and the development of new approaches to teaching future historians. The research will help identify main problems and highlight growth points in high school historical education, which will contribute to enhancing the quality of training professionals in the field of history and strengthening the position of historical knowledge in society.Scientific Novelty. The scientific novelty of this research lies in its comprehensive approach to analyzing the state of university historical education in the Republic of Belarus against the backdrop of modern challenges. The work proposes a systematic categorization of key problematic issues and trends characteristic of this sphere, taking into account the specifics of the national educational space. Particular attention is paid to the introduction of innovative teaching methods, integration of digital technologies, and the formation of interdisciplinary connections.The author concludes that successfully overcoming current challenges and realizing the prospects of university historical education in the Republic of Belarus are possible if a comprehensive approach is adopted, considering national characteristics and traditions. This approach involves modernizing curricula with an emphasis on the country's cultural and historical heritage, implementing innovative pedagogical technologies adapted to local conditions, and strengthening interdisciplinary ties within the educational environment. An essential direction remains the integration of digital learning and adaptation of educational standards to global competition requirements while preserving national identity and values. These measures will enhance the quality of training specialists in history and strengthen the position of historical knowledge in society, contributing to the formation of a coherent picture of the past and present necessary for the sustainable development of the Republic of Belarus.
Keywords: Belarus; higher education; university; history department; historical education